KONDISI PENGELOLAAN, PENDIDIK, DAN SARANA PRASARANA SEKOLAH DASAR NEGERI DI PROVINSI BANTEN - Sugilar (Jurnal Pendidikan, 2010)
The purpose of this study is to describe the condition of the management, educators and infrastructure of public primary schools in Banten province based on the parameters of national education standards. The samples of this study consisted of 78 in many schools under studied. The standards that were achieved in the areas of management such as self-evaluation and its utilization for school development planning do not apply optimally. Also teacher educational qualifications and in-job-training, and infrastructure or facilities. The study recommended that those specific matters would be the main concern in future educational improvement in Banten province.